Strategy for Household Survival of Unlicensed Gold Mining Workers (PETI) in Nagari Lubuk Gadang Timur, South Solok Regency - Gian Aprianata; Sri Rahmadani; Wibi Wijaya (CV. Rayyan Dwi Bharata, 2023)
This research is motivated by PETI workers who experience economic problems in household life, where the income earned by PETI WORKERS is not sufficient for household needs. Where the average income of PETI workers is Rp. 1,000,000. per month, however, PETI workers continue to work even though work as PETI workers is at high risk, namely raids from the government. The problem in this research is that gold mining without a permit (PETI) is illegal and can also damage the environment. So that the apparatus conducts raids once a month, which are carried out a maximum of two weeks in a month. Therefore this study aims to describe the household survival strategies of unlicensed gold mining workers (PETI). The theory used in this research is Max Weber's social theory. The method used in this study is a qualitative approach with a descriptive type to describe the problem under study. Retrieval of informants using purposive sampling with a total of 15 informants. There are two types of data in this study, namely primary data and secondary data. The research data was collected using observation techniques, interviews and document studies. Data analysis was carried out by collecting data, reducing data, presenting data and drawing conclusions using the unit of analysis in this individual study. Based on the results of the research that has been conducted, it was found (1) that PETI labor is the main job in fulfilling the household economy of Jorong Sungai Aro. (2) There are 3 livelihood strategies for PETI workers. The first strategy is to optimize family potential, the form of family potential optimization strategy used by the Jorong Sungai Aro household is that the wife helps her husband work vegetables and children who sometimes during school holidays help the family by becoming working PETI. Second, the strategy of minimizing expenses with a priority scale is carried out by getting used to living frugally. The third is utilizing social networks by borrowing money from neighbors, paying at stalls or shops and so on. The strategy for utilizing social networks that is usually carried out by poor families is to borrow money from neighbors or family and borrow money from food stalls to buy basic foodstuffs.